2021
DOI: 10.1021/acs.jpcc.0c10367
|View full text |Cite
|
Sign up to set email alerts
|

Facile Crystallization of Ice Ih via Formaldehyde Hydrate in Ultrahigh Vacuum under Cryogenic Conditions

Abstract: Although hexagonal ice (ice Ih) is the most common and highly studied crystalline form of ice, its nucleation from clathrate hydrates is poorly understood. Here, we report the formation of ice Ih through the dissociation of formaldehyde hydrate, prepared under ultrahigh vacuum (UHV) in the temperature window of 130–135 K. This unique route for crystallization is highly facile, and it occurs below the usual crystallization temperature of ice Ih of 155 K in UHV; the associated activation energy is also lower. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 48 publications
2
30
1
Order By: Relevance
“…The set-up has been used extensively to study molecular solids. 6,7,12,49,50 UHV was maintained by using several turbomolecular pumps backed by oil-free diaphragm pumps (Pfeiffer Vacuum). Pressure was monitored by a Bayard-Alpert gauge (Pfeiffer Vacuum), controlled by a MaxiGauge controller (Pfeiffer, Model TPG 256 A).…”
Section: Methodsmentioning
confidence: 99%
“…The set-up has been used extensively to study molecular solids. 6,7,12,49,50 UHV was maintained by using several turbomolecular pumps backed by oil-free diaphragm pumps (Pfeiffer Vacuum). Pressure was monitored by a Bayard-Alpert gauge (Pfeiffer Vacuum), controlled by a MaxiGauge controller (Pfeiffer, Model TPG 256 A).…”
Section: Methodsmentioning
confidence: 99%
“…Among all the microcapsules, the 15% crosslinkers was the optimum concentration to strengthen the shells rmly, thus holding the LO core up to 73%. Based on the Avrami equation, [44][45][46][47] the release rate constant of the microcapsules with 15% crosslinkers was the lowest one out of the others (Table 3). According to the computed n value of Avrami's equation, the LO release mechanism was ruled by the rst-order kinetics for all microcapsules.…”
Section: Microcapsule Characterizationmentioning
confidence: 99%
“…In UHV, CHs of acetone and formaldehyde were converted to cubic and hexagonal ices upon dissociation of the hydrate cages. 21,26 Also, it has been observed that ice XVI can be created by subjecting neon hydrate to pumping in a vacuum. 27 astrochemical environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dissociation of these hydrates could lead to the formation of crystalline ice. In UHV, CHs of acetone and formaldehyde were converted to cubic and hexagonal ices upon dissociation of the hydrate cages. , Also, it has been observed that ice XVI can be created by subjecting neon hydrate to pumping in a vacuum . Physical properties such as density and refractive index of such ice forms may have important relevance for planetary objects.…”
Section: Introductionmentioning
confidence: 99%